The Role of Virtual Reality as a Promotion Tool to Increase Travel Interest during the Covid 19 Pandemic: A Phenomenological Approach of Tourist Objects in Jakarta - Iwan Sukoco,; Suparman, Suparman; Bambang Hermanto,; Rivani, Rivani (Technium Social Sciences Journal, 2021)
This study is aimed at answering the question of how Indonesians are interested in traveling during a pandemic, and how virtual reality is applied as a promotional tool in order to attract people to travel. This is a qualitative research with a phenomenological approach. The data collection was carried out by in-depth interviews with 22 participants who were classified into 3 categories of ages, namely Gen Z (5-25 years), Gen Y / Millennial (26-40 years), Gen X (41-55 years). This study proves that conducting tourism promotion using Virtual Reality (VR) is proven to be effective, as long as it fulfils 4 important elements of VR, namely: virtual world, which is a content that creates a virtual world in the form of screenplay and script, immersion, namely the sensation that brings technology users VR feels that it is in a real environment even though it is fictitious or not real, sensory feedback serves to convey information from the virtual world to the user's senses. These elements include visual (sight), audio (hearing) and touch, interactivity, is one of the most important elements in VR because VR simulates a real-world sensation for its users. and if the simulated virtual world is rigid and there is no interaction, the resulting sensation is not optimal.